Teachers’ Views on Online Learning Implementation in the Primary School Context in North Bali - Putu Rahmayanti (International Journal of Digital Learning on Languages and Arts (IJODLLA), 2024)
The rapid shift of face-to-face learning to online learning brings many issues to all level of education. Primary school as the first level of formal education gets some challenges in its implementation. The compatibility of online learning especially for the lower graders (1st, 2nd, 3rd) are questioned. Therefore, the present research is aimed at analyzing teachers’ perception on the compatibility of online learning for the elementary students. Through descriptive qualitative model from Creswell (2014), the responses from the teachers collected and analyzed. There were three teachers from three primary schools in Singaraja used as the respondents in the present study. From the knowledge of the teachers, most of them were familiar with blended learning because before the outbreak they frequently used it to teach the students. In addition, most of the primary school teachers perceived that students in grade 1, 2 and 3 actually do not suitable with online learning. Yet, in the pandemic situation, all learning activities implemented through online platform. Further, the teachers viewed that elementary school students still need direct guidance from the teachers and real practice in the school. However, the implementation of online learning especially in primary education need to be prepared well and get support from patents at their home.